Analysis of Financial Performance of BPKPAD Klaten Regency for the 2018-2022 Fiscal Year - Syamsi, Lathifah Nur; Hananto, Santoso Tri; Jannah, Miftahul; Hantoro, Sri (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2023)
This present study aims to seek out the result of the analysis of the budget realization report of Klaten Regency for the 2018-2022 fiscal year to assess its financial performance. The quantitative descriptive analysis method was utilized in this study. The data were the budget realization report of Klaten Regency for the 2018-2022 fiscal year. The data were collected from Regional Income and Asset Financial Management Agency (Indonesian: Badan Pengelolaan Keuangan Pendapatan dan Aset Daerah, abbreviated BPKPAD) Klaten Regency by using documentation techniques and library research in research journal literature. The results show that based on the variance analysis, regional revenue and expenditure are included in the Good (Favorable) category. Based on the income growth ratio analysis, the result tends to decrease and is categorized as negative. The result of the expenditure growth ratio shows there is an increase and is categorized as positive. Meanwhile, looking at the regional expenditure compatibility ratio analysis, the result shows operating expenditure is more dominant than capital expenditure. Based on the findings, the author advises the Klaten Regency Government to make efforts to maximize various sources of regional revenue as well as allocate regional expenditure appropriately to avoid waste of funds to realize positive growth in revenue and expenditure and create a balance in regional expenditure.